IRF3 Negatively Regulates Toll-Like Receptor-Mediated NF-κB Signaling by Targeting TRIF for Degradation in Teleost Fish - Zhao, Xueyan; Huo, Ruixuan; Yan, Xiaolong; Xu, Tianjun (Frontiers in Immunology, 2018)
NF-κB signaling is tightly regulated and essential to innate and adaptive immune responses, its regulatory mechanism remains unclear in various organisms, especially teleosts. In this study, we reported that IRF3 can negatively regulate TRIF-mediated NF-κB signaling pathway. Overexpression of IRF3 can inhibit TRIF-mediated NF-κB signaling pathway. However, knockdown of IRF3 had an opposite effect. IRF3 can promote the degradation of TRIF protein in mammal and fish cells, but this effect could be inhibited by MG132 treatment. Furthermore, we found that the inhibitory effect of IRF3 primary depended on its IAD domain. IRF3 is crucial for the polyubiquitination and proteasomal degradation of TRIF. Our finding indicates that IRF3 negatively regulates TLR-mediated NF-κB signaling pathway by targeting TRIF for ubiquitination and degradation. This study provides a novel evidence on the negative regulation of innate immune signaling pathways in teleost fish and thus might provide new insights into the regulatory mechanisms in mammals.